ANALYSIS OF HUMOR IN MOTHER-DAUGHTER CONVERSATION IN GILMORE GIRLS SEASON 3 - Idrus, Sheila; Nurfadhilah, Auliyanti Sahril (Journal of English Literature and Linguistic Studies, 2025)
This study aims to analyze the type of humor used in the series Gilmore Girls season 3. This research has two main objectives: to classify the types of verbal humor by using Shade's theory (1996) and to find out the violation of conversational maxim based on Grice's cooperative principle theory (1989). This research uses qualitative descriptive method. The results show that there are several types of humor types, joke, satire, parody, anecdote, farce, irony, sarcasm, tall tale and wit. This study also identified various maxim violations in the conversation, including maxim of quantity, maxim of quality, maxim of ration and maxim of manner. The results of this study show that tall tale and wit are the most frequently used types of humor in the Gilmore Girls season 3 series, reflecting the tendency of Lorelai and Rory's humor style in using exaggerated imagination and response. in using exaggerated imagination as well as quick and witty responses to create a light, warm, and entertaining conversational atmosphere.